The downs and ups of the consumer price index in Argentina: From National Statistics to Big Data - Lury, Celia; Gross, Ana (PARTECIPAZIONE E CONFLITTO, 2014)
On the 5th of February 2007, the Institute of National Statistics and Census in Argentina (INDEC) released a press statement, giving a percentage figure for that month’s Consumer Price Index (CPI-GBA). Since the announcement, this number and its subsequent variations have been at the centre of a national and international political, legal and technical controversy. The legitimacy of the numerical value of the percentage has been called into question by a range of actors and has been challenged by the emergence of multiple alternative indicators of inflation. We explore this methodological controversy through the lens of statactivism. We do not describe the controversy in its entirety, but, rather, enter the controversy to develop a comparison of the procedures informing the production of the CPI as a national statistic with those informing its production as a big data number. In both cases, we explore the way in which price is produced as an indicator. In doing so we draw attention to the significance of calculative infrastructures as ubiquitous, multi-layered processes of connectivity, that have the capacity to make surfaces, to draw lines and boundaries, and to enable particular economic and political activities to unfold in multiple and specific ways. We argue that the capacity to connect, to attach and detach, that is immanent to such infrastructures configures price as an indicator in particular ways, and in doing so help make what we call state space, a term which we use to draw attention to how specific configurations of connectivity in the calculative infrastructure enacts a space of possibility for statactivism